Results of sclerotherapy and mucopexy with haemorrhoidal dearterialization in II and III degree haemorrhoids. A 4 years' single centre experience - Lobascio, Pierluigi; Laforgia, Rita; Pezzolla, Angela (Frontiers in Surgery, 2023)
Introduction Haemorrhoidal disease (HD) affects a considerable portion of the adult population. The aim of this study is to confirm the safety and efficacy of the treatments and to report the long-term outcomes of Sclerotherapy (ST) and Mucopexy and Haemorrhoidal Dearterialization (MHD) performed over the last 4 years in a single tertiary centre. The secondary outcome is to evaluate the usefulness of both techniques and to demonstrate how those can be associated as a bridge to surgery. Materials and methods Patients affected by second–third-degree haemorrhoids and undergoing ST or non-Doppler guided MHD between 2018 and 2021 were enrolled. Safety and efficacy, recurrence rate, Haemorrhoid Severity Score (HSS) and pain resulting from both techniques were evaluated. Results Out of 259 patients, 150 underwent ST. Further, 122 (81.3%) patients were male and 28 (18.7%) were female. The mean age was 50.8 (range 34–68) years. Most of the patients (103, 68.6%) were affected by second-degree HD, while 47 (31.4%) were affected by third-degree HD. The overall success rate was 83.3%. The median pre-operative HSS score was 3 (IQR 0–4, p = 0.04) and at 2 year the median HSS was 0 (IQR 0–1, p = 0.03). No intraoperative complications and no drug-related side effects occurred. The mean follow-up for ST was 2 years (range 1–4; SD ±0.88). MHD was performed on 109 patients. In detail, 80 patients (73.4%) were male while 29 patients (26.6%) were female. The mean age in this group was 51.3 (range 31–69). Further, 72 patients (66.1%) were affected by third-degree HD and 37 (33.9%) by second-degree HD. The median HSS score was 9 (IQR 8–10, p = 0.001) preoperatively two years after treatment was 0 (IQR 0–1, p = 0.004). Major complications occurred in three patients (2.75%). The overall success rate was 93.5% (second degree 89.2% vs. third degree 95.8%). The mean follow-up for MHD was 2 years (range 1–4; SD ±0.68). Conclusions The results confirm the usefulness of those techniques, which can be considered safe and easily repeatable procedures, with a low recurrence rate after 2 years of median follow-up.